Práticas de letramento na interação em sala de aula : a constituição de uma comunidade de leitores no 5º ano do ensino fundamental - Bryan, Kaluana Nunes Bertoluci (2015)
The objective of this dissertation which is from Applied Linguistic field was written to discuss about practices of literacy in class interaction trying to analyze how is constituted reader´s community of a fifth grade in a elementary public school from countryside of São Paulo. Since we admit reading as a social and historical literacy practice (KLEIMAN, 2010) whom its teaching was historically institutionalized by school (CHARTIER, 2004 ; HERBRARD, 2007; HILSDORF, 2012) and which defines its particularities inasmuch it is a surface of the human activity (DIONISIO, 2000; BUNZEN, 2010), we tried to analyze the practices of reading teaching considering visible and implicit elements which brought meaning to them by observing the teacher´s conceptions about reading and readers education and how she shares these meanings with her students. Thereunto, we structured an epistemological transdisciplinary box and we approach our research object in a interpretative speech perspective with ethnographic profile because this is a qualitative research guided by a social and historical view. We keep a semester involved with the community researched staying in field for a month and recording 17 classes in audio type. Beyond recordings we used interviews, we used document analysis (reading contents), field reports which were systematized in event maps and others with distinct nature. The research logic, based on “Ethnographic Research Cycle”, helped us to orient our job proposing analytic questions as from the study of data found during the research. Our analysis pointed to two significative practices in that reading community: Reading Corner and Shared Reading which evidence the teacher´s conceptions and shared meanings about reading as the importance of its taste and habits, the element and strategies of access to materials as an essential factor on reading education, the valorization of literature reading and the importance attributed to fluent reading done aloud. In this community, reading is conceived as a research, entertainment and knowledge socializing practice furthermore it is an important moralizing tool. These results show how complex are literacy practices and docent´s job such as the importance of their analysis inside real contexts and as multifaceted elements.